A utilização dos processos referenciais em textos sobre moda da revista Select - Armelin, Cristina Silva dos Santos (2014)
This dissertation analyze the different reference strategies used in texts with fashion theme of the Select magazine and describes the functionalists of this strategies. To reach this descriptions and analyzes, it make use of the theoretical reference assumed on the functionalist perspective and Textual Linguistics, due to the fact that the Functionalism considers the language a instrument which delivers the user a execution of its communicative purposes, besides of to consider the aspects of the used language, assign to it the character of social activity and a tool of interaction. Whatever the Textual Linguistic, become evident the fact of this theoretical perspective which dedicates to study not just the principles that construct the text and the factors which involve the production and the reception of this text, but also to return to the interaction process established between the author, the reader and the text, showing that this interaction occurs in certain context. Before, the Textual Linguistic believes that the textual ability of the speaker allows that he is capable to produce coherent texts and not just a pile of phrases and words. On this side, verifies like the linguistic choices of its authors select the possibles readers of this texts and how this choices could generate possibles directions of interpretation. The corpus of this research structures in sixteen articles and four editorials published on Select magazine among the months of august of 2013 and may of 2014. In a first moment, it was executed the collection and the selection of the texts, which ones, forward, were studied by quantity-quality analyze, to ensure what are the referential strategies most used and how they could conduct the interpretation of the readers. This collected data are showed, objectively, in boxes that appear soon after the development of the analyzes. In between of the quantity analyze, it have showed until now, a big utilization of meronymies (34 in the articles and 33 in the editorials), indirect anaphoras (30 occurrence in the articles and 19 in the editorials), pronouns (55 uses in the articles and 34 in the editorials) and encapsulating anaphoras (28 in the articles and 23 in the editorials), been that the last one is a referential process which re categorize precedent or subsequent information and, for this reason, could show/influence opinions. The quantity analyze allowed to demonstrated that the accounted referential process contribute with the referral process, once that, according to Mondada and Dubois (2003), enables the reconstruction of speech-objects in the moment of enunciation.